Modeling the effects of carriers on transmission dynamics of infectious diseases - Darja Kalajdzievska; Michael Yi Li (Mathematical Biosciences and Engineering)
An $S$-$I_c$-$I$-$R$ epidemic model is investigated for infectious diseases that can be transmitted through carriers, infected individualswho are contagious but do not show any disease symptoms. Mathematical analysis is carried out that completely determines the globaldynamics of the model. The impacts of disease carriers on the transmission dynamics are discussed through the basic reproductionnumber and through numerical simulations.